How to connect with nature - Gooley, Tristan, ....- (London : Macmillan, 2014)
Transform the way you view and experience the natural world A deep knowledge of our natural environment is no longer a vital part of everyday survival, certainly for those of us living in cities and working in weatherproof offices. Unless we have an inherent love of the great outdoors, do we really need to connect with nature? Tristan Gooley believes that real connection, no matter how small, can enrich us as individuals, allowing us to see every living thing in its own intricate network. Offering a host of techniques, he helps us awaken our senses and deepen our understanding of nature's cycles, conflicts, and relationships. By cultivating the right mindset we can gain a better appreciation of the world, both indoors and outdoors.
Keywords: Leren filosoferen